Spinal GABA transporter 1 contributes to evoked-pain related behavior but not resting pain after incision injury - Pradier, Bruno; Segelcke, Daniel; Reichl, Sylvia; Zahn, P. K.; Pogatzki-Zahn, E. M. (Frontiers in Molecular Neuroscience, 2023)
The inhibitory function of GABA at the spinal level and its central modulation in the brain are essential for pain perception. However, in post-surgical pain, the exact mechanism and modes of action of GABAergic transmission have been poorly studied. This work aimed to investigate GABA synthesis and uptake in the incisional pain model in a time-dependent manner. Here, we combined assays for mechanical and heat stimuli-induced withdrawal reflexes with videobased assessments and assays for non-evoked (NEP, guarding of affected hindpaw) and movement-evoked (MEP, gait pattern) pain-related behaviours in a plantar incision model in male rats to phenotype the effects of the inhibition of the GABA transporter (GAT-1), using a specific antagonist (NO711, at 10, 20 and 40µg). Further, we determined the expression profile of spinal dorsal horn GAT-1 and glutamate decarboxylase 65/67 (GAD 65/67) by protein expression analyses (n=20) at four time points post-incision. Four hours after incision, we detected an evoked pain phenotype (mechanical, heat and movement), which transiently ameliorated dose-dependently following spinal inhibition of GAT-1. However, the NEPphenotype was not affected. 4h after incision, GAT-1 expression was significantly increased, whereas GAD 67 expression was significantly reduced. Our data suggest that GAT-1 plays a role in balancing spinal GABAergic signaling in the spinal dorsal horn shortly after incision, resulting in the evoked pain phenotype. Increased GAT-1 expression leads to increased GABA uptake from the synaptic cleft and reduces tonic GABAergic inhibition at the post-synapse.Inhibition of GAT-1 transiently reversed this imbalance and ameliorated the evoked pain phenotype.